World and Russian Market of Mergers and Acquisitions - N. S. Zagrebel’Naya (Vestnik MGIMO-Universiteta)
This article analyzes the global and Russian markets of mergers and acquisitions (M&A). The article also presents the dynamics of M&A deals in the world and in Russia for the period 2010-2014, the geography of transactions and their sectoral structure. The overall analysis is supported by the examples of ten largest M&A deals in the world and in Russia, committed in 2014. In the market economy many companies, mostly large, consider M&A as means to improve the material and the production sector, increase profitability, sustainability, creating a positive image. Such transactions could improve a company's development, make business more competitive and profitable. In today's global economy we could observe the growing trend of global integration, which is manifested in the access of various types of companies into new markets, as well as the concentration of capital and consolidation of business, on the one hand. However, on the other hand, there is deterioration in the conditions of the companies due to the ongoing financial, economic and political crises and economic sanctions. This leads to changes in the activity on the world and Russian markets of M&A. Thus, to study its dynamics and trends in the contemporary world and in Russia is one of the most important and actual issues.